Study of Custom Hiring Centre(CHC) in Meghalaya : an economic analysis - Bhuyan, Ipshita; N. Anandkumar Singh (Umiam : CPGSAS, CAU(Imphal), 2024)
Custom Hiring Centre (CHC) is a unit consisting of a set of farm machinery, implements, and equipment which are provided to the farmers at affordable prices on a hiring basis. About 84 per cent of the land holdings in India are below 1 ha which makes the individual ownership of agricultural machinery uneconomic and operationally unviable (Gol, 2019). CHCs therefore serve as best alternative in enabling easy availability of farm machineries to improve the farm productivity and reduce the cost of cultivation of the small and marginal farmers. During 2021, the total number of CHCs in India was 78,117 with Punjab state having the highest number of CHCs i.e., 22,800 and the lowest in Meghalaya with only three CHCs (Gol, 2021). Meghalaya is basically an agrarian state with 81 per cent of the population depending on agriculture for their livelihood. The concept of CHC is new to the state. Though only three CHCs were established till 2021, establishment of more number of CHCs has been constantly increasing (GoM, 2023). With this background, the study has been undertaken to explore the effect of CHC in the state of Meghalaya with the following objectives: (1) To study the economic feasibility of Custom Hiring Centre in Meghalaya, (2) To assess the impact of Custom Hiring Centre on farm profitability and (3) To analyze the constraints faced by different stakeholders of Custom Hiring Centre. Proportionate random sampling was applied to a sample of 100 respondents for collecting primary data. To achieve the above mentioned objectives, financial methods such as discounting methods which include Net Present Value (NPV), Benefit - Cost Ratio (BCR), Internal Rate of Returns (lRR), cost concepts, descriptive statistics, etc. were applied. The study revealed that CHC in Meghalaya is economically feasible as B-C ratio was greater than one, NPV was positive and IRR was greater than the opportunity cost of capital. The beneficiaries were found to have lesser cost of cultivation as compared to non- beneficiaries which was due to significant difference in requirement of human labour. This showed that farm mechanization reduces the drudgery of labour. Non availability of well trained technical man power, non availability of machineries during the peak season and lack of awareness about the CHC were the major constraints faced by the CHC managers, beneficiaries and non-beneficiaries respectively. Hence, providing training programs to the farmers on use of machinery and creating awareness about the CHC would help in persuading more number of farmers to hire machineries from the CHC thereby reducing their cost of cultivation and increasing their profit.
Includes bibliographical references.
Keywords: Custom Hiring Centre (CHC) -- Meghalaya